2020
DOI: 10.30738/tc.v4i1.7286
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Model Cooperative Learning Tipe Make a Match Terhadap Hasil Belajar Ipa Pada Siswa Kelas v Sd Muhammadiyah Karangploso

Abstract: The background of this study is the low value of students in science subjects. The purpose of this research is to determine the effectiveness of the application of the Make A Match cooperative learning model to the learning outcomes of the fifth grade science students at Muhammadiyah Elemantary School of Karangploso. This research is quasi-experimental, with Pretest Posttest Control Group Design. The population is  all of fifth grade students which is  consisted of two classes with a total of students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
1
0
4
Order By: Relevance
“…(2-tailed) value on the pretest and posttest data is 0.000 <0.05, then H0 is rejected and Ha is accepted, so it can be concluded that the Make A Match type cooperative learning model assisted by Purama media has an effect on science learning outcomes on ecosystem material. These results are in line with research conducted by Purwanti & Saputri (2020) which states that the cooperative learning model of the make a match learning type is effective in learning towards student learning outcomes in science subjects in grade V of elementary school. The use of this model also makes the learning atmosphere in the classroom more enjoyable because there are elements of games, competition between students and awards (Suprapta, 2020).…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…(2-tailed) value on the pretest and posttest data is 0.000 <0.05, then H0 is rejected and Ha is accepted, so it can be concluded that the Make A Match type cooperative learning model assisted by Purama media has an effect on science learning outcomes on ecosystem material. These results are in line with research conducted by Purwanti & Saputri (2020) which states that the cooperative learning model of the make a match learning type is effective in learning towards student learning outcomes in science subjects in grade V of elementary school. The use of this model also makes the learning atmosphere in the classroom more enjoyable because there are elements of games, competition between students and awards (Suprapta, 2020).…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Sebagian besar siswa menyatakan bahwa minat terhadap pelajaran IPA rendah dikarenakan IPA merupakan pelajaran yang rumit. Penelitian yang dilakukan oleh (Purwanti, 2018) memperoleh hasil penelitian bahwa Faktor penyebab kesulitan belajar yaitu dari dalam diri siswa yaitu faktor intelegensi, dan faktor dari luar yaitu dari guru tentang metode pembelajaran.…”
Section: Kesulitan Siswa Dalam Menyelesaikan Soal Fisikaunclassified
“…Dalam pembelajaran tatap muka, kreativitas seorang guru sangat diperlukan guna terciptanya proses belajar yang aktif dan efektif dalam upaya mengembangkan motivasi dan kemampuan siswa. Guru juga memiliki peran yang sangat penting dalam membantu optimalisasi kemampuan siswanya (Purwanti & Saputri, 2020). Untuk mendukung kegiatan belajar yang tidak membosankan dan monoton guru perlu memanfaatkan teknologi.…”
Section: Pendahuluanunclassified